LANGUAGE LEARNING STYLES AND STRATEGIES: A BRIEF REVIEW - Novita, Loly (Menara Ilmu, 2018)
Styles and strategies used in language learning actually different in terms, however, they giveeffects to the success of language learners. The learning styles comes from personalityvariables. Take for example; psychology, cognitive make up, socio-culture background andeducational experience. Learning strategies relates to the behaviour or thought of learners toenhance their own learning. The functions of learning strategies is to make language learningeasier, faster, more enjoyable, more self-directed, more effective, and more transferrable. Thecombination of language learning styles and strategies will create more independent andautonomous learners.Keywords: Learning Styles, Learning Strategies, and Implication of Learning Stylesand Strategies in L2Teaching.